Language processing in social context - Dietrich, Rainer; Graumann, Carl F. (Elsevier Science, 1989)
The book presents an interdisciplinary analysis of social, cognitive, situational and contextual aspects of language and language processing by first and second language speakers. Linguists and psychologists formulate theoretical models and empirical analyses of the influence of such factors on various levels of language processing. These relate specifically to syntactic and semantic parsing, lexical selection, and text production. The issue of "hearer orientation'' in language use lies at the forefront of interest in this anthology and is tackled from such different fields as linguistics, te
Gesehen am 15.04.2020
Description based upon print version of record
Keywords: Aufsatzsammlung; Pragmatik; Psycholinguistik; Kontext; Sprache